Crystals, x-rays and proteins comprehensive protein crystallography - Sherwood, Dennis; Cooper, Jon (Jonathan B.) (Oxford : Oxford University Press, 2011)
Information derived from X-ray crystal structures of biological molecules allows us to explain their functions in living organisms and to develop drugs to treat disease. This book describes the principles and practice of X-ray diffraction as a key technique at the forefront of new discoveries in biology and medicine.
Description based on print version record.
Includes bibliographical references and index.
Keywords: X-rays -- Diffraction; X-ray crystallography; Proteins -- Analysis